2022
DOI: 10.1210/jendso/bvac006
|View full text |Cite
|
Sign up to set email alerts
|

Role of ZBTB38 Genotype and Expression in Growth and Response to Recombinant Human Growth Hormone Treatment

Abstract: Background SNPs in ZBTB38 have been associated with idiopathic short stature (ISS) and adult height. This study sought to a) characterise the phenotype of ISS patients and their response to recombinant human growth hormone (rhGH) by ZBTB38 SNP genotype b) describe the relationship of ZBTB38 expression with normal growth and c) describe the in vitro effects of ZBTB38 knockdown on cell proliferation and MCM10 expression. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several studies have revealed that ZBTB38 ( Cibz / Zbtb38 in the mouse) regulates cell proliferation, growth, and differentiation [ 24 , 29 , 30 , 33–41 ]. The function of ZBTB38 in cell growth is complex as its depletion (or genetic inactivation) can either promote, reduce, or not affect cell proliferation according to cell types, which echoes its potential function as an oncogene or tumour suppressor in cancers [ 32 , 33 , 35 , 36 , 38 , 42–45 ]. Further highlighting the pleiotropic, context-specific, and tissue-specific effects of ZBTB38 , many single-nucleotide polymorphisms (SNPs) either within or in close proximity to ZBTB38 have been associated with adult height and many diseases including idiopathic short stature, atopic dermatitis, macular degeneration, osteoporosis, prion disease, and prostate cancer [ 42 , 46–56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that ZBTB38 ( Cibz / Zbtb38 in the mouse) regulates cell proliferation, growth, and differentiation [ 24 , 29 , 30 , 33–41 ]. The function of ZBTB38 in cell growth is complex as its depletion (or genetic inactivation) can either promote, reduce, or not affect cell proliferation according to cell types, which echoes its potential function as an oncogene or tumour suppressor in cancers [ 32 , 33 , 35 , 36 , 38 , 42–45 ]. Further highlighting the pleiotropic, context-specific, and tissue-specific effects of ZBTB38 , many single-nucleotide polymorphisms (SNPs) either within or in close proximity to ZBTB38 have been associated with adult height and many diseases including idiopathic short stature, atopic dermatitis, macular degeneration, osteoporosis, prion disease, and prostate cancer [ 42 , 46–56 ].…”
Section: Introductionmentioning
confidence: 99%